On the asymptotic expansion of the logarithm of Barnes triple gamma function II - Koumandos, Stamatis; Pedersen, Henrik L. (MATHEMATICA SCANDINAVICA, 2017)
The remainders in an asymptotic expansion of the logarithm of Barnes triple gamma function give rise to completely monotonic functions of positive order.